Production of fatty acid methyl ester biofuel from low value waste vegetable oil using acid catalyst - Azifah Ibrahim (School of Bioprocess Engineering, University Malaysia Perlis, 2013)
Production of Fatty Acid Methyl Ester (FAME) from low value waste vegetable oil using acid catalyst is further described in this work. The raw materials used in this study, which is the waste cooking oil (WCO) is collected and is used for the feedstock of producing FAME by acid-catalyzed transesterification. The effect of oil to alcohol molar ratio and the effect of amount of catalyst on the production of FAME is discussed in details. Alcohol used in this work is methanol while sulphuric acid is used as the catalyst. By varying three different molar ratio (1:6, 1:9 and 1:12) and three different amount of catalyst (1 wt %, 2 wt % and 4 wt %), the yield and conversion of FAME is studied. Acid-catalyzed transesterification is performed for 10 hours at 60 p0sC. WCO is first filtered and analysed for its physical characteristics before proceeding with transesterification reaction. FAMEs produced from the reactions are then analysed for its physical characteristics and Gas Chromatography is used to analyse its contents. Acid-catalyzed transesterification using 1:12 molar ratio with 4 wt % of catalyst produced the most FAME yield and conversion. Using the parameter, techno economic analysis is done by perfoming simulation using SuperPro Designer 7.0. The biodiesel production unit cost obtained is RM1.93/kg.